Chemical composition of essential oil extracted from lavender growing in Kastamonu, Türkiye - Tahmas Kahyaoğlu, Deren; Özen, Mürüvvet Begüm; Yıldız, Hilal (Turkish Journal of Forestry, 2023)
Lavender and lavender oils have been used as traditional herbal medicines for centuries. Nowadays, lavender and its essential oil are valuable materials used in many industries, e.g., food, cosmetics, perfume, sanitary products, and pharmaceuticals. Since the components of valuable oil differ depending on the growing region, these components must be identified to ascertain the oil's quality and potential uses. The essential oil composition was obtained from the stemmed fresh flowers of Kastamonu, Türkiye cultivars of lavandin (Lavandula x intermedia var. Super) via a Clevenger-type hydrodistillation apparatus. Then, the essential oil was analyzed by gas chromatography-mass spectrometry (GC-MS), and 14 components were identified. Linalool and linalyl acetate were the main components, with 28.44% and 17.12%, respectively. In this study, we aimed to evaluate our results by comparing them with Pharmacopoeia Europaea and ISO standards to determine the quality of the essential oil and its possible areas of use. The findings of this study showed that lavandin essential oil is a high-quality essential oil as it contains high levels of linalool and is free of camphor. In addition, while the linalool, terpinen-4-ol, and camphor contents of the variety complied with the lavender oil standards set by ISO 3515:2002, the linalyl acetate content was found below this. Due to its high linalool content and lack of camphor, the extracted lavandin oil can be predicted to be suitable for use in the food, beverage, aroma, pharmaceutical, perfume and aromatherapy industries.
Keywords: lavandula sp.; linalool; linalil asetat; Forestry; Hidrodistilasyon; Lavandula sp.; Linalil asetat; Linalool; hydrodistillation; linalyl acetate; Ormancılık Ürünleri Kalitesi Değerlendirmesi; SD1-669.5; Hydrodistillation; Lavandula sp.; Linalyl acetate; Linalool; hidrodistilasyon; Forestry Product Quality Assessment; 3. Good health